PERSONAL CHARACTERISTICS OF PSYCHOLOGICAL COUNSELING CLIENTS - Turakulov , Ulugbek; Erkinboyeva, Kholida (Science technology&Digital finance, 2024)
A deep understanding of the personal characteristics of customers is the key to effective psychological counseling. Given the variety of personality aspects, the consultant can build reliable relationships, choose the best work methods and help the client achieve the necessary changes. This article details the following.